2018
DOI: 10.1007/s10584-018-2269-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring temperature-related mortality using endogenously determined thresholds

Abstract: Heat-related mortality tends to be associated with heatwaves that do not allow for sufficient acclimatisation to hot weather. In contrast, damage functions and most heatwave emergency response plans do not account for acclimatisation. Using an excess heat measure that accounts for acclimatisation, this paper produces estimates of temperature-related mortality for the five largest Australian capital cities. Fixed effects panel threshold regressions are applied to establish the thresholds that coincide with heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…Two separate thresholds were used to define “hot days”: (1) days with an EHI_A ≥ 4, and (2) days with an EHI_A ≥ 7, based on use in a prior study [7]. It was decided to use these same thresholds after eyeballing Fig 1 (see Results section), which did not identify alternative EHI_A thresholds associated with clear increases in the mean number of ED attendances in the selected regions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two separate thresholds were used to define “hot days”: (1) days with an EHI_A ≥ 4, and (2) days with an EHI_A ≥ 7, based on use in a prior study [7]. It was decided to use these same thresholds after eyeballing Fig 1 (see Results section), which did not identify alternative EHI_A thresholds associated with clear increases in the mean number of ED attendances in the selected regions.…”
Section: Methodsmentioning
confidence: 99%
“…This regression approach has been used to investigate whether there are thresholds that are relevant to the number of daily ED services. Thresholds have been found for temperature-related mortality using a similar approach in [7] and this analysis focuses on whether the same is true for ED services. These regressions were performed in Stata using the ‘threshold’ command with the data specified as time-series data for each hospital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the association between X and Y is usually modelled nonlinearly, it has been shown that it can be well approximated by a piecewise linear function (Cheng et al, 2019;Longden, 2018;Masselot et al, 2018). Thus, we consider the following model:…”
Section: The Threshold Modelmentioning
confidence: 99%
“…En términos epidemiológicos, la asociación entre la temperatura y la mortalidad humana ha sido intensamente estudiada (Yang y Jensen, 2017; Gosling et al, 2017;Bell et al, 2008;Lomgden, 2018;Marsha et al, 2018), entre los argumentos se menciona que el calor puede provocar un incremento en la mortalidad, sobre todo en zonas urbanas, debido a la mayor concentración de construcciones y al hacinamiento. Se ha asociado también en zonas donde el calor se relaciona con un incremento de los casos de malaria (Jonathan et al, 2018).…”
unclassified